Q. 154.4( 23 Votes )

# Divide the polynomial p(x) = x^{4} – 3x^{2} + 4x + 5 by g(x) = x^{2} + 1 – x and find the quotient and remainder.

Answer :

We have, p(x) = x^{4} – 3x^{2} + 4x + 5 and g(x) = x^{2} – x + 1

By long division method we have,

Quotient = x^{2} + x − 3

Remainder = 8

Rate this question :

Divide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{3} – 3x^{2} + 4x + 2 , g(x) = x – 1

Divide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{3} – 3x^{2}– x + 3, g(x) = x^{2} – 4x + 3

When a polynomial p(x) is divided by (2x + 1), is it possible to have (x - 1) as a remainder? Justify your answer.

RS Aggarwal - MathematicsDivide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{4} + 2x^{3} – 3x^{2} + x – 1, g(x) = x – 2

Find all the zeroes of the polynomial given below having given numbers as its zeroes.

x^{4} – 6x^{3} – 26x^{2} + 138x – 35;2±√3

p(x) = x^{6} + 3x^{2} + 10 and g(x) = x^{3} + 1

p(x) = x^{4} + 1, g(x) = x + 1

Verify that are the zeroes of the cubic polynomial p(x) = 3x^{2} – 5x^{2} – 11x – 3 and then verify the relationship between the zeroes and the coefficients.

Find all the zeros of the polynomial, if two of its zeros are √3 and .

RD Sharma - Mathematics